Photonic density of states and photonic bandgap of deformed titanium dioxide inverse opal structure - Sitpathom N. (2023)
Titanium dioxide (TiO2) inverse opal, a well-ordered nanoporous media, has a good potential in light-matter enhancement application. In this work, the fabricated TiO2 inverse opal structures were prepared by well-ordered template from convective deposition. This measured photonic bandgap was shorter in wavelength from the theoretical prediction of the perfect well-ordered pore structure due to structural shrinkage and incomplete matrix fill. Shorter lattice distance from shrinkage and lower refractive index of matrix from incomplete-filled structure resulted in higher eigen energies of photonic crystal. The scanning electron microscope images indicated that the pore size of TiO2 inverse opal was reduced around 39% from the initial template size. Additionally, to explore the detail on photonic bandgap shift of deformed inverse opal, the photonic band-structures and density of states (DOS) spectra under variation of refractive index and fill fraction were evaluated by plane-wave expansion method. It was found that the zero DOS range has a narrow bandwidth at low fill fraction and refractive index of the matrix which agreed with the perturbation theory on the Hermitian Maxwell eigenvalue problem.